POLYMORPHISM OF RYRI, ESR, MC4R AND LEP GENES IN PIG MICRO-POPULATION OF LARGE WHITE BREED OF UKRAINIAN SELECTION - Matiiuk, V. V.; Saienko, A. M.; Usenko, S. O.; Khalak, V. I. (Scientific Progress & Innovations, 2020)
Genetic and population analysis of RYRI, MC4R, LEP and ESR gene polymorphism for Large White breed of pigs of Ukrainian selection was performed. Traditional breeding methods, based on the assessment of animals for their own productivity and the productivity of offspring, do not always provide the expected genetic progress. Advances in molecular genetics in recent years, the development of DNA marker systems of various classes give breeders a new powerful tool for analyzing the genotypes of animals, which allows for selection based on objective genetic information. Particular attention is paid to the so-called SNP markers, the nature of which is associated with single nucleotide polymorphism of DNA in the structural or regulatory parts of genes involved in the control of important economic and biological characteristics of animals. Such genes include RYRI, ESR, MC4R and LEP. DNA typing was performed in the genetics laboratory of the Institute of Pig Breeding and Agro-Industrial Production. For the study, DNA was used, which was isolated from the bristles of pigs of Large White breed in LLC “Druzhba-Kaznacheiivka”, including124 heads. DNA typing was performed using PCR-RFLP. In the micropopulation of the Large White breed there is a certain polymorphism in the genes ESR, MC4R and LEP. All experimental animals in the RYRI gene are monomorphic and had the genotype p.1843CC, a variant of the mutant allele was absent. The presence of a significant amount of allele B-0.61, (61 %) and high frequencies of genotypes BB and AB (0.42 and 0.38), which are associated with high rates of sow multiplicity, allow to select animals by the desired genotypes to increase reproductive rate in sows of the studied micro-population. Quite a high level of homozygous TT genotypes with a frequency of 0.85 leptin gene affected the possibility of its using in marker selection of the animals. A sufficient level of the index of polymorphic information content of PIC by genes ESR and MC4R indicates that marker selection of Large White breed in LLC “Druzhba-Kaznacheiivka”is possible.